Characterization and Regulation of Protease Synthesis and Activity in Bacillus licheniformis - Bernlohr, R. W. (1971)
Extracts of growing and sporulating cells contain a protease activity that has a broad pH optimum and an unusually broad specificity. The activity, which resides in at least two protein fractions, hydrolyzes all peptide bonds and can reduce a mixture of proteins into a mixture of free amino acids with a high efficiency. No inhibitors of the activity were found, but the protease showed a definite preference for denatured protein as substrate. The synthesis of the intracellular protease activity is under catabolite repression control, as is the extracellular activity. However, the synthesis of the two activities is not coordinate, making the relationship between the two unclear. Due to (i) the specificity of the intracellular activity, (ii) the fact that it is synthesized most rapidly under slow or nongrowing conditions, and (iii) our inability to measure in vivo protein turnover in cells containing high levels of enzyme, a scavenger role is postulated for the enzyme. The rate of protein turnover is not a function of the protease content of the cells.